Protein phasing at non‐atomic resolution by combining Patterson and VLD techniques. (1st July 2014) - Caliandro, Rocco; Carrozzini, Benedetta; Cascarano, Giovanni Luca; Comunale, Giuliana; Giacovazzo, Carmelo; Mazzone, Annamaria
<x xml:space="preserve">Abstract</x> Phasing proteins at non‐atomic resolution is still a challenge for any ab initio method. A variety of algorithms [Patterson deconvolution, superposition techniques, a cross‐correlation function (C map), the VLD (vive la difference) approach, the FF function, a nonlinear iterative peak‐clipping algorithm (SNIP) for defining the background of a map and the free lunch extrapolation method] have been combined to overcome the lack of experimental information at non‐atomic resolution. The method has been applied to a large number of protein diffraction data sets with resolutions varying from atomic to 2.1 Å, with the condition that S or heavier atoms are present in the protein structure. The applications include the use of ARP/wARP to check the quality of the final electron‐density maps in an objective way. The results show that resolution is still the maximum obstacle to protein phasing, but also suggest that the solution of protein structures at 2.1 Å resolution is a feasible, even if still an exceptional, task for the combined set of algorithms implemented in the phasing program. The approach described here is more efficient than the previously described procedures: e.g. the combined use of the algorithms mentioned above is frequently able to provide phases of sufficiently high quality to allow automatic model building. The method is implemented in the current version of SIR2014.